Decreased TREC and KREC levels in newborns with trisomy 21 - Marakhonov, Andrey; Mukhina, Anna; Vlasova, Elena; Efimova, Irina; Balinova, Natalya; Rodina, Yulia; Pershin, Dmitry; Markova, Zhanna; Minzhenkova, Marina; Shilova, Nadezhda; Mudaeva, Dzhaina; Saydaeva, Djamila; et al. (Frontiers in Pediatrics, 2024)
Newborn screening (NBS) for severe combined immunodeficiency (SCID) has been widely implemented to enable early detection and intervention. Trisomy 21, commonly known as Down syndrome (DS), poses unique challenges in NBS due to its frequent association with T and/or B cell lymphopenia. The pilot NBS screening program recently conducted in Russia was aimed to identify both severe T and B cell deficiencies by measuring TREC and KREC. This study aims to evaluate the incidence of DS in newborns who participated in the pilot program, assess their TREC and KREC values, and determine the proportion of DS newborns potentially identifiable through T/B lymphopenia NBS. We conducted a retrospective analysis of the data obtained during the pilot NBS program, involving 202,908 newborns from eight regions of Russia. The study identified 157 patients with trisomy 21 among the screened cohort, resulting in a DS birth prevalence of 1:1284. Median TREC and KREC values did not significantly differ between full-term and pre-term subgroups of DS patients. TREC values in DS newborns were decreased and comparable to those of the extremely preterm newborns. DS newborns also demonstrated significant differences in KREC values as compared to the general cohort regardless of gestational age. Our data suggests abnormalities of Tand B-cell lineages development and requires further investigation. This article highlights the need for increased awareness of the intrinsic immunological defects associated with DS. The findings underscore the importance of continued follow-up and comprehensive support by healthcare teams for individuals with DS.